Dynamic changes of microbial community and moisture ratio during bio-drying of sludge after electro-dewatering. (15th December 2022) - Li, Qian; Zhang, Keqiang; Yang, Zengjun; Guo, Haigang; Zheng, Xiangqun; Zhang, Qiangying; Xiong, Jian; Lu, Xuebin
Abstract: Using electro-dewatering as the pretreatment process for sludge bio-drying can improve the dewatering performance. It was innovatively investigated including the microbial mechanism and the kinetics of moisture removal by bio-drying with electro-dewatered sludge in this study. Two bio-drying processes using electro-dewatered sludge (EDS) and sludge added cornstalk conditioner (CSS) were compared. Microbial community analysis showed that the abundance of Bacteroidetes increased from 4.21% to 16.67% after electro-dewatering. The dominant phyla were Bacteroidetes (36.79%), Proteobacteria (32.35%), and Actinobacteria (24.58%) at the end of EDS bio-drying. Network analysis revealed that the co-occurrence patterns in EDS included 40 nodes and 97 edges. The prediction results of the Kyoto Encyclopedia of Genes and Genomes demonstrated that the relative abundances of carbohydrate metabolism and metabolism of terpenoids and polyketides in sludge decreased, while the relative abundances of lipid metabolism, xenobiotic biodegradation and metabolism increased after electro-dewatering. Five thin layer drying kinetic models were analyzed to estimate the bio-drying kinetic parameters. The Page's model could be better fitted to the results and the highest R 2 was 0.9570 in the EDS. The new coefficients k (0.1637) and n (1.2097) were obtained. The results provided mechanism and data support for exploring and applying bio-drying technology after sludge electro-dewatering. Graphical abstract: Image 1 Highlights: Drying kinetics and microbial community in EDS was researched for the first time. Compared with CSS treatment, EDS had better bio-drying effect. The Page's model was proved to be suitable for sludge bio-drying kinetics. The number of overlapping OTUs in the CSS system was 179 more than the EDS. The metabolic function accounted for the highest proportion in sludge bio-drying.